FOTOGRAFI URBAN LANDSCAPE DENGAN MENGGUNAKAN KAMERA LOMO - Rahmad, Cito Yasuki (Institut Seni Indoensia Surakarta, 2010)
Landscape photography is not a new thing in photography. It is similar to the temple or street photography, only that the objects in focus are in urban regions. By using lomography camera the urban landscapes are captured in special manners that new, extraordinary images appear. They are like unnatural colour, fish eye effects, and others. Keywords: Urban landscape, Lomography